Prevalence and risk factors for back pain in sports: a systematic review with meta-analysis - Wilson, F.; Ardern C. L.; Hartvigsen, J.; Dane, K.; Trompeter, K.; Trease, L.; Vinther, A.; Gissane, C.; McDonnell, S. J.; Caneiro, J. P.; Newlands, C.; Wilkie, K.; et al. (British Journal of Sports Medicine, 2021)
Objectives: We aimed to determine the prevalence of low back pain (LBP) in sport, and what risk factors were associated with LBP in athletes.